Environmental assessment of aviation transport processes quality component environment - Франчук, Г.М.; Антонов, А.М.; Маджд, С.М.; Загоруй, Я.В. (Proceedings of National Aviation University (archive), 2006)
In the article the actual problem of today – the air-transport processes’ influence on quality of the environmental components is considered. The necessity of realization of the ecological evaluation of a condition of the environment is analysed and argued by realization of monitoring researches. The conformity of certain concentration of pollutants to fixed standards is compared and coordinated.